Abnormal Terminal Vertebral Artery in Atlantoaxial Dislocation: A Rare Case Report (Bangladesh Journal of Neurosurgery, 2022)
Atlantoaxial dislocation (AAD), is a challenging disorder of the craniocervical junction. Because of its deep location and intricate anatomic structure, the craniocervical junction is always a difficult region for spine surgery. (1) Risk of vertebral artery injury makes the surgery difficult. Patient having an abnormal vertebral artery, like our patient, makes the situation more complicated.Bang. J Neurosurgery 2022; 11(2): 118-121